Democracy and Judicial Review: Playing Waldron's Game - Osowski, Igor (My University, 2015)
The decision to adopt a formalized charter of rights is a momentous expression of a nations commitment to according and protection certain rights for its citizens. They usually contain complex and ambiguous moral concepts about which people have good faith disagreements. This thesis examines and ultimately rejects the belief put forward by Jeremy Waldron that judicial review is only democratically justifiable if the power of the last word in the interpretation of statutes and charter rights belongs to the democratically appointed legislature instead of the appointed judiciary. This thesis argues that a procedural conception of democracy is too limited and we would do better to base a justification of judicial review using a constitutional conception of democracy. It matters less which party has the authority of the final say with respects to rights-determining decisions and more on whether or not the democratic principle of equal concern for all is satisfied. This thesis introduces the concepts of deference, constitutional conventions, and principles and argues that these, among other things, will inform the constitutional theorists about which powers are actually present in a practice of judicial review. Once the contours of the practice are filled out one can then begin to deliberate about whether a particular conception of judicial review has democratic justification.
Keywords: Democracy and Judicial review; commonwealth model; Gardbaum; Waldron; Waluchow; weak and strong form